Empowering MSMEs through English Learning Training to Improve Digital Communication Competence - Setianingsih, Tri; Imansyah, Imansyah; Kamarudin, Kamarudin; Wulandari, Yayang Erry; Utama, I Made Permadi (Lumbung Inovasi: Jurnal Pengabdian kepada Masyarakat, 2025)
The limited English proficiency of most Micro, Small, and Medium Enterprises (MSMEs) became the background for this community service program. This activity aims to improve the quality of human resources, particularly in mastering English as a global language as well as digital communication competence, among young MSME entrepreneurs. Jatisela Village, located in Gunungsari District, is a developing area with many MSME players and is close to Senggigi Beach, a well-known tourist destination visited by both domestic and international tourists. Unlike conventional language training, this program combines LSP-based English learning with peer mentoring and digital artifact production to address the specific needs of rural MSMEs. The implementation involved several stages, including surveys, task distribution, execution, and monitoring. The activities included material sharing, practice sessions, and discussions. A pre-test was conducted before the training, and a post-test afterward to measure participants’ progress. Continuous monitoring was carried out by the team. The pre-test results showed that only 30% of the 20 participating MSME entrepreneurs were able to communicate in English, both orally and in writing, with foreign tourists, while 70% were unable to do so.The training employed a diffusion method focused on English conversation for buying and selling offers to improve digital marketing skills. The sessions combined lectures, question-and-answer discussions, hands-on practice, and finally, a post-test and evaluation. The post-test results showed an improvement of 40%, with 70% of participants becoming more confident and capable of communicating in English both orally and in writing, while 30% still required further guidance. The evaluation results indicated that nearly 100% of participants were satisfied with the program.